Serum caspase-cleaved cytokeratin (M30) indicates severity of liver dysfunction and predicts liver outcome - Oweira, Hani; Sadeghi, Mahmoud; Daniel, Volker; Mieth, Markus; Zidan, Ahmed; Khajeh, Elias; Ghamarnejad, Omid; Fonouni, Hamidreza; Weiss, Karl Heinz; Schmidt, Jan; Lahdou, Imad; Mehrabi, Arianeb (Annals of transplantation, 2018)
[b]BACKGROUND[/b] - The Model for End-Stage Liver Disease (MELD) score is a well-established tool for assessing hepatic failure. The present retrospective study investigated whether serum keratin 18 (M65) and caspase-cleaved cytokeratin (M30) were associated with liver dysfunction and post-transplant graft failure. - [b]MATERIAL AND METHODS[/b] - A total of 147 patients with liver cirrhosis were categorized into 2 groups according to their baseline MELD score (group I: MELD score <20, n=87, and group II: MELD score ≥20, n=60). Serum M65 and M30 levels were measured by ELISA. - [b]RESULTS[/b] - Cirrhotic patients had significantly higher serum M65 and M30 levels than healthy controls (p<0.0001). Serum M65 was correlated with the MELD score and serum bilirubin (p≤0.007) and serum M30 was correlated with the MELD score, international normalized ratio, and serum bilirubin (p≤0.001). Group II had significantly higher serum M65 and M30 levels than group I (M65, p=0.025 and M30, p<0.001). Patients who lost the allograft during the first post-transplant year had significantly higher serum M30 levels than patients with a graft survival of >1 year (p=0.004). In the regression analysis, serum M30 was associated with the MELD score (odds ratio [OR]=2.545, p=0.005), serum bilirubin (OR=2.605, p=0.005) and 1-year graft loss (OR=3.61, p=0.006). - [b]CONCLUSIONS[/b] - Our data indicate that serum M30 levels reflect the degree of liver dysfunction and can predict 1-year graft loss.